A Comparative Study of Chinese Idiomatic Expressions in Modaozushi and Its Thai Translation "The Untamed" - Lervalann, Sayada (Journal of Social Sciences and Humanities Research in Asia, 2022)
The objectives of this research were to study the characteristics of language structure and intention of using the meaning of Chinese idioms in Modaozushi(魔道祖师),and comparing it to the Thai translation version, "The Untamed". This descriptive research compiled 332 expressions of Chinese idioms from Modaozushi Vol. 1, and 13 expressions from "The Untamed" Vol. 1, with the aim of analyzing the language structure and intention of using the Chinese idiomatic expressions. Then, the Chinese idiomatic expressions in Modaozushi were analyzed and compared to those in the Thai translation version, "The Untamed". The research results showed that the grammatical structure of the Chinese idiomatic expressions in Modaozushi were classifed into seven categories, which were related to the elements of subject and predicate structure, verb and object structure, serial verb structure, parallel structure, main and modification structure, serial verb structure, and complex sentence structure. The intentions of using the meaning in Modaozushi were classified into five categories namely the Chinese idiomatic expressions with the intention of warning, sarcasm, reproach, admiring, and showing opinion. The translation of such idioms in Modaozushi was divided into three types, which were the translated idioms, non-translated idioms, and Thai idioms translated from the non-Chinese idiomatic expressions. The translated idioms were classified into three sub-types involving paraphrase, restatement translation, and substitute translations.